Patient experience of medication administration and development of a Patient Experience and Preference Questionnaire (PEPQ) for patients with advanced or metastatic cancer - Skalicky, Anne; Bennett, Bryan; Raimbourg, Judith; Lonardi, Sara; Correll, Julia; Lugowska, Iwona; Dixon, Matthew; Sargalo, Nashmel; Martin, Mona L. (Frontiers in Pharmacology, 2024)
Introduction: A better understanding of patient experience of intravenous (IV) or subcutaneous (SC) routes of administration is fundamental to providing optimal administration of medical therapies to oncology patients. The objective of this study was to examine patient experiences of IV and SC treatment with nivolumab and confirm the relevance of item concepts in the Patient Experience and Preference Questionnaire (PEPQ). The PEPQ is a clinical outcomes assessment instrument developed to obtain patient-centric data and understand the experience with IV and SC treatment administration. Methods: Embedded qualitative interviews were conducted with a subset of participants from three treatment cohorts with metastatic non-small cell lung cancer (NSCLC), renal cell carcinoma (RCC), unresectable or advanced metastatic melanoma, hepatocellular carcinoma (HCC), or colorectal cancer (CRC) from the CA209-8KX clinical trial. The concept elicitation interviews were conducted within 14 days of the initial treatment cycle and assessed patient experiences with IV and SC administration. Concepts from interviews were mapped to the PEPQ version 1.0 questions to assess relevance and convergence of concepts. Results: Interviews were conducted with 43 trial participants from clinical sites opting to participate from six countries (Argentina, France, Netherlands, Poland, Spain, and New Zealand). The mean age of sub-study participants was 66 ± 11.3 years (range 24–80 years) and 67.4% (N=29) were male. Sub-study participants with experience of SC most frequently reported symptoms or signs of injection-related redness (27.9%), itching (14.0%), and pain (of needle), and described the pain as pricking, stinging or tingling (11.0% each). Amount of pain and time burden were widely endorsed as important factors for satisfaction and related to route of medication administration. For 11 sub-study participants with experience with both IV and SC, 10 (90.9%) preferred SC over IV administration. Conclusion: This study summarizes the experience and satisfaction of receiving IV or SC treatment and confirms the relevance of the PEPQ in a subgroup of CA209-8KX clinical trial participants with metastatic NSCLC, RCC, melanoma, HCC, and CRC. Participant treatment experience and satisfaction with route of medication mapped to the PEPQ question content support the relevance of the PEPQ v2.0 in clinical trials as a self-report measure.